2020
DOI: 10.1016/j.heliyon.2020.e05572
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics contamination in the soil from Urban Landfill site, Dhaka, Bangladesh

Abstract: Microplastics (MP) pollution has become a matter of global concern because of its several deleterious effects on environmental health, especially on the terrestrial environment. The evidence of MP contamination in terrestrial environment is less explored compared to aquatic bodies. However, in Bangladesh despite having high possibility of MP contamination, there is lacking of available research-based evidence. Urban areas soil is subjected to act as a major environmental reservoir for MPs. Thus, this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(16 citation statements)
references
References 69 publications
(113 reference statements)
1
15
0
Order By: Relevance
“…As for Bangladesh, among the different categories of waste that are dump in solid waste landfill, on an average around 4% of it comprises polythene and plastic (Alam and Qiao 2020 ). In the very recent time, soil samples were collected from the Amin bazar landfill sites and the presence of microplastic has been identified in the form of low density polyethylene (LDPE), high density polyethylene (HDPE), and cellulose acetate (CA) (Afrin et al 2020 ). Hence, we can hypothesize the possibility of release microplastic and micropollutants from the landfill leachate of the dumping site in Bangladesh to the receiving water body and thereby bioaccumulation in aquatic species (Parvin et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As for Bangladesh, among the different categories of waste that are dump in solid waste landfill, on an average around 4% of it comprises polythene and plastic (Alam and Qiao 2020 ). In the very recent time, soil samples were collected from the Amin bazar landfill sites and the presence of microplastic has been identified in the form of low density polyethylene (LDPE), high density polyethylene (HDPE), and cellulose acetate (CA) (Afrin et al 2020 ). Hence, we can hypothesize the possibility of release microplastic and micropollutants from the landfill leachate of the dumping site in Bangladesh to the receiving water body and thereby bioaccumulation in aquatic species (Parvin et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Contamination of MPs in urban soils around a landfill site in Dhaka, Bangladesh confirmed the presence of low-density polyethylene (LDPE) and high-density polyethylene (HDPE) MPs and demonstrated that landfill can be a source of MPs dispersing to the surrounding soils (Afrin et al, 2020). MPs in soil can be transported and circulated to other environmental compartments and may reach water resources, sediments and living organisms (Facchinelli et al, 2001;Keshavarzi et al, 2019;Afrin et al, 2020). It is still unknown if MPs will be incorporated in the dynamic structure of the soil and if they will be bioaccessible and affect environmental health in a significant way , Afrin et al, 2020.…”
Section: Introductionmentioning
confidence: 94%
“…Microplastics (MPs), which can be defined as synthetic solid particles or polymer matrices with a size range of 1 µm -5 mm and insoluble in water (Arthur et al, 2009), are emerging and ubiquitous contaminants that have become an environmental challenge (Afrin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer types of the microplastics were expressed as polyethylene and cellulose acetate. The particle diameter of the microplastics detected in the soil beneath the landfill was within the range of 0.001–2 mm [ 101 ].…”
Section: Solid Waste Disposal Facilities and Their Potential Role As A Source For Microplasticsmentioning
confidence: 99%